An Overview of Erithocyt Index among Stroke Patients In Kraton Regional Hospital, Pekalongan - Wibowo, Subur; Agustina Lestari, Anggun (INDOGENIUS, 2025)
Background & Objective: Stroke is a serious health condition that requires immediate treatment. It occurs when blood supply to the brain is interrupted due to blockage or rupture of blood vessels in the brain, resulting in cell death in certain areas of the brain. This study aims to determine the erythrocyte indices (MCV, MCH, MCHC) in stroke patients. Method: The study design was descriptive, with a sample size of 24 participants. Total sampling was used for sample selection. The study was conducted at the inpatient ward of Kraton District General Hospital, Pekalongan Regency, from January to February 2025. Data analysis was performed using descriptive and analytical methods, presented in tables and narrated. Result: The study results showed that MCV levels were normal (80.00 μL/mL – 100.00 μL/mL) in all 24 samples (100%), with an average value of 85.32 μL/mL.  The majority of MCH levels showed normal results (27.00 pg – 31.00 pg) in 18 samples (75%), 3 samples (12.5%) with low values, and 3 (12.5%) samples with high values, with an average value of 34.32 pg. The majority of MCHC levels showed normal results (30.00–35.00 g/dL) in 15 samples (62.5%), 9 samples had high values, and there were no low results, with an average value of 29.2 g/dL. Conclusion: The conclusion of this study is that the average results of MCV, MCH, and MCHC in the respondents were normal.